2015
DOI: 10.5194/isprsarchives-xl-7-w3-85-2015
|View full text |Cite
|
Sign up to set email alerts
|

Rice Crop Monitoring and Yield Estimation Through Cosmo Skymed and TerraSAR-X: A SAR-Based Experience in India

Abstract: ABSTRACT:Rice is the most important cereal crop governing food security in Asia. Reliable and regular information on the area under rice production is the basis of policy decisions related to imports, exports and prices which directly affect food security. Recent and planned launches of SAR sensors coupled with automated processing can provide sustainable solutions to the challenges on mapping and monitoring rice systems. High resolution (3m) Synthetic Aperture Radar (SAR) imageries were used to map and monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…All the six-multi temporal features concisely characterized the key information in the maize signature. Hence, the values of multi-temporal features derived were used in classification of maize pixels in the study area and maize area map was generated which was in line with work reported by Pazhanivelan et al (2015).…”
Section: Multi-temporal Features Extractionmentioning
confidence: 68%
See 2 more Smart Citations
“…All the six-multi temporal features concisely characterized the key information in the maize signature. Hence, the values of multi-temporal features derived were used in classification of maize pixels in the study area and maize area map was generated which was in line with work reported by Pazhanivelan et al (2015).…”
Section: Multi-temporal Features Extractionmentioning
confidence: 68%
“…The backscatter minimum was observed in the initial acquisition, indicating emerging condition of the crop and the backscatter increased in succeeding acquisitions indicating the growth of the crop. (Pazhanivelan et al, 2015) and groundnut (Deiveegan et al, 2017) under Tamil Nadu condition. The minimum of -21.26 and -14.05 under VH and VV polarization at emerge stage indicates the presence of favorable soil moisture conditions caused by sowing rains during D 1 to D 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a promising result, given that there have already been researchers and development practitioners working on the ground in India and other countries (largely in southeastern Asia) piloting remote sensing for rice yield prediction to eventually inform crop insurance programs. 5 The predictive accuracy of the remote sensing technologies has been rather encouraging, with predictive accuracy ranging between 85 percent and 96 percent across three sites in Tamil Nadu, India when predictions were made at the block (sub-district administrative unit), compared with accuracy of 87 percent when predictions were made at the district level (Pazhanivelan et al, 2015). Other recent research has found remote sensing yield prediction accuracy in rice as high as 95 percent in China (Huang et al, 2013).…”
Section: Determinants Of Wtpmentioning
confidence: 99%
“…Remote Sensing plays a very important role in achieving the United Nations Sustainable Development Goal 2: Zero Hunger. Crop monitoring provides timely information about the crop conditions at various stages and helps to estimate area and yield at national and even village levels (Pazhanivelan et al, 2015). Yield information is very useful in checking the price fluctuations of food crops and monitoring the food reserves.…”
Section: Introductionmentioning
confidence: 99%